Influence of fiber surface treatment on the tribological properties of Calotropis gigantea plant fiber reinforced polymer composites. Issue 9 (1st June 2021) - Ramesh, Manickam; Deepa, Chinnaiyan; Rajeshkumar, Lakshminarasimhan; Tamil Selvan, Manickam; Balaji, Devarajan
Abstract: Recent era witnessed a tremendous growth in utilization of plant fibers to make composite materials, and their industrial applications have multiplied many folds. All these utilizations were kindled by the advantageous features of the plant fibers and their potential to substitute the currently used synthetic fibers in almost all the applications. Current work falls in line with the abovementioned statements, and Calotropis gigantea fibers (CGFs) are reinforced with epoxy matrix to fabricate composite materials. The fiber surfaces were modified with sodium hydroxide (NaOH) and potassium permanganate (KMnO4 ) solutions. The CGFs reinforced composites with epoxy matrix were fabricated with the aid of compression molding technique and the samples were subjected to wear tests. The effect of fiber surface modification over the tribological characteristics of these composites such as frictional force, coefficient of friction, and rate of wear was evaluated by varying the time of wear from 40 to 1040 s at an interval of 40 s. From the results, it is found that the weight loss varies between 0.0013 and 0.0018 g . Scanning electron microscopy studies are also carried out to observe the surfaces of the samples before and after wear tests. Experimental results portrayed that NaOH treated CGF composites rendered better tribological behavior when compared with untreated and KMnO4 treated CGF composites. Abstract : Current work falls in line with the above statements and Calotropis gigantea fibers (CGFs) are reinforced with epoxy matrix to fabricate composite materials. The fiber surfaces were modified with sodium hydroxide (NaOH) and potassium permanganate (KMnO4 ) solutions. The CGF reinforced composites with epoxy matrix were fabricated with the aid of compression molding technique and the samples were subjected to wear tests.